Long‐Term Efficacy of Annual Bluegrass Control Strategies on Golf Course Putting Greens. Issue 1 (14th February 2019) - Patton, Aaron J.; Braun, Ross C.; Schortgen, Geoffrey P.; Weisenberger, Daniel V.; Branham, Bruce E.; Sharp, Bill; Sousek, Matthew D.; Gaussoin, Roch E.; Reicher, Zachary J.
Abstract : Core Ideas: Aerification of golf course putting greens in the summer rather than in the early fall does not decrease annual bluegrass cover. Monthly applications of iron sulfate were ineffective at reducing annual bluegrass. Methiozolin, paclobutrazol, or bispyribac‐sodium provided the greatest reduction of annual bluegrass when used over multiple years. Annual bluegrass ( Poa annua L.; ABG) is among the most common weeds of highly maintained turf in the United States. Though many labeled active ingredients exist for control in golf course fairways, few labeled options exist for putting greens. Further, ABG has demonstrated resistance to several herbicide modes of action commonly used on fairway turf. The use of a systems approach coupling cultural and chemical controls with diverse modes of action could limit the potential for further ABG resistance development. Our objective was to evaluate a systems approach to ABG control on putting greens by examining seven season‐long programs of plant growth regulators, herbicides, and/or iron sulfate fertilizer with July or September hollow tine aerification over 2 or 4 years in three Midwestern US states. Aerification timing did not influence annual bluegrass cover at any of the three locations. The effectiveness of season‐long treatments varied by location, but methiozolin, paclobutrazol, or bispyribac‐sodium consistently reduced ABG. Monthly applications of iron sulfate alone did not effectively control ABG. Several treatments reduced ABG, but none completely removed annual bluegrass. Currently, methiozolin and bispyribac‐sodium are not registered for use on putting greens in the US but show potential to control ABG. As such, paclobutrazol was the most effective product of those tested that is currently available for use on US putting greens. Future availability of herbicides such as methiozolin and bispyribac‐sodium would provide needed options to allow for the rotation or addition of multiple‐control strategies in an ABG control system to limit resistance development.